1994
DOI: 10.1037/0022-0663.86.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive profiles of reading disability: Comparisons of discrepancy and low achievement definitions.

Abstract: The assistance of John Holahan, who bore responsibility for maintaining and updating the database, is gratefully acknowledged. Thanks are also due to Lois Dreyer, who supervised the testing of the children. In addition, we acknowledge many others at the Yale University Center for the Study of Learning and Attention Disorders and at Haskins Laboratories, whose help was essential to the completion of the project. Finally, we thank Linda Kimbrough for her work on preparation of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

46
391
1
9

Year Published

1996
1996
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 509 publications
(447 citation statements)
references
References 78 publications
46
391
1
9
Order By: Relevance
“…In general, absolute gains are large even when a child is mildly mentally retarded, or fits a "learning disability" profile of age/IQ discrepancies to reading scores. This confirms other research that has shown the discrepancy measure to be invalid as a diagnostic criteria for a "learning disability" or "dyslexia" (Fletcher et al 1994;Stanovich and Siegel 1994). In fact, our results challenge the notion of a spedal reading disability such as "dyslexia," confirming the conclusions of Slavin and his group (Slavin, Karweit, and Wasik 1994) who argue that all children, barring the mentally retarded, can be taught to read if the reading program and the method of delivery are effective.…”
Section: Discussionsupporting
confidence: 77%
“…In general, absolute gains are large even when a child is mildly mentally retarded, or fits a "learning disability" profile of age/IQ discrepancies to reading scores. This confirms other research that has shown the discrepancy measure to be invalid as a diagnostic criteria for a "learning disability" or "dyslexia" (Fletcher et al 1994;Stanovich and Siegel 1994). In fact, our results challenge the notion of a spedal reading disability such as "dyslexia," confirming the conclusions of Slavin and his group (Slavin, Karweit, and Wasik 1994) who argue that all children, barring the mentally retarded, can be taught to read if the reading program and the method of delivery are effective.…”
Section: Discussionsupporting
confidence: 77%
“…In addition, IQ-achievement discrepancy scores were not significantly correlated with initial growth in reading performance following one semester of one-to-one tutoring (Vellutino, Scanlon, & Lyon, 2000; see also Share, McGee, & Silva, 1989). Presently, there is a large body of research showing that children with IQ discrepant and IQ non-discrepant reading scores cannot be adequately differentiated, vis-à -vis response to instruction or prognosis (see Francis, Fowler, & Shaywitz, 1994;Fletcher et al, 1994Fletcher et al, , 2002Lyon et al, 2001Lyon et al, , 2002Vellutino, Scanlon, & Lyon, 2000). There are also two recent meta-analyses showing null to small differences between the cognitive skills of these two populations (Hoskyn & Swanson, 2000;Steubing et al, 2002).…”
Section: Dyslexia Across the Life-spanmentioning
confidence: 99%
“…In other words, problems in performing and applying PA capabilities are at the heart of most children's reading difficulties, regardless of other types of language and cognitive difficulties (Phillips, Clancy-Menchetti, & Lonigan, 2008). Additional studies (e.g., Ashour, 2011;Bradley & Bryant, 1983;Bruck, 1992Bruck, , 1993Fawcett & Nicholson, 1995;Fletcher et al, 1994;Fox & Routh, 1980;Lindamood, Bell, & Lindamood, 1992;Lyon, 1995) have shown the significance of PA in the assessment and remediation of the individuals who have difficulty in reading (Ehri et al, 2001). …”
Section: Pa and Dyslexiamentioning
confidence: 99%